Occurrences of 29 pesticides in the Huangpu River, China: Highest ecological risk identified in Shanghai metropolitan area. (July 2020) - Xu, Lei; Granger, Caroline; Dong, Huiyu; Mao, Yuanxiang; Duan, Shule; Li, Jin; Qiang, Zhimin
Abstract: To investigate the occurrence and risk of pesticides in the Huangpu River basin, spatial and temporal concentration variations of 29 commonly used pesticides and their risk quotient (RQ) values for three different trophic organisms (fish, daphnia, green algae) from 16 sampling sites were conducted in 2018–2019. These 29 pesticides include 4 carbamates, 2 benzimidazoles, 6 neonicotinoids, 2 organophosphates, 9 triazoles, and 6 others. Of the 29 pesticides analyzed, 18 were present in every sample taken from the Huangpu River. The concentration of target pesticides in water samples ranged from < LOQ (for buprofezin in summer, autumn, and winter) to 607.30 ng L −1 (for carbendazim in spring). From the source (i.e., Taihu Lake) to the estuary of the Huangpu River, with the exception of isocarbophos and isoprothiolane (gradual decrease), the spatial variation of target pesticide concentrations firstly exhibited an increasing trend and then a decreasing trend. Peak spatial variation was seen in metropolitan area, which is closely related to the type of land use and the discharge of tributaries. In addition, the total summed concentration of the 29 pesticides during winter (1037.60 ng L −1 ) was higher than summer (788.82 ng L −1 ) in rural and metropolitan areas. For the ecological risk assessments of fish, daphnia, and green algae, the triazoles, carbamates, neonicotinoids were risk-dominant pesticides, respectively. Notably, carbendazim had a 100% detection frequency and the highest concentration of the 29 pesticides analyzed, indicating its high consumption in the Huangpu River basin. Graphical abstract: Image 1 Highlights: Carbendazim showed the highest concentration of the 29 pesticides. The type of land use and the contribution of tributaries impacted the spatial variations. The highest pesticide concentration and risk were observed in metropolitan area.